‘More construction than destruction’: the ambiguous place of architectural heritage in a reconstructing Belfast circa 1972-89 - Mcclelland, Andrew (International Planning History Society Proceedings, 2016)
The urban landscape of the city of Belfast was radically transformed from the late 1960s by a combination of state-sponsored reconstruction and civil unrest, including paramilitary activity associated with the period in Northern Ireland euphemistically known as the Troubles. This paper explores the sometimes competing and contradictory interpretations of destruction in the built environment as the UK government sought to promulgate a narrative of progressive change in the fortunes of Belfast in the face of a prolonged terrorist campaign, with the discussion partially framed using Vale’s ideas on the social construction of urban resilience. The narrative is illuminated by the case of the Castlecourt development in the heart of the city in the 1980s, which was controversial for its demolition of prominent Victorian-era buildings. The paper addresses the political questions of the ambiguous place of architectural heritage in Belfast circa 1972-89, who dominated power relations in the city, and who benefited from key redevelopment decisions. It provides insights with contemporary resonance into the critical importance of institutional architecture and governance to the setting of government priorities and the application of power in conflicted places.